A novel credential protocol for protecting personal attributes in blockchain. (May 2020) - Singh, Kalpana; Dib, Omar; Huyart, Clément; Toumi, Khalifa
Highlights: A novel user-centric and privacy preserving scheme is proposed over the blockchain. Users self-blind their sensitive attributes to access services over the blockchain. Service providers can check the authenticity of users' claims. A privacy-preserving online trading system is implemented by our approach. Experimental results show the feasibility of the proposed work. Abstract: This paper proposes a novel user-centric and privacy-preserving credential scheme over the blockchain. The proposed protocol allows users to access services without revealing sensitive attributes. This new paradigm is based on an efficient short signature, which uses pairing and self-blindable credentials that are verifiable on the blockchain. Our scheme achieves the advanced features of anonymity, unlinkability, and untraceability of users. Moreover, confidentiality of users' attributes and unforgeability of their credentials are met. We provide security proofs and a real-world use-case where the protocol can be applied. To empirically assess the performance of our solution, the cryptographic components and communications between the various involved actors are implemented using GO and Java. In addition, an implementation for an online trading use case based on Hyperledger Fabric is provided. Finally, we prove the efficiency of our work by presenting some experimental results and exhibiting comparisons with known traditional credentials schemes.